THE PRODUCTIVITY OF QUAILS FED WITH DRAGON FRUIT PEEL JUICE FERMENTED THROUGH DRINKING WATER - M. L., Santoso; Dewi, G. A. M. K.; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
This research aims to determine the productivity of quail given fermented dragon fruit peel juice in drinking water for 4 weeks. This research used a Completely Randomized Design (CRD) consisting of 3 treatments and 6 replications, each replication using 10 birds so that 180 quail were used. The treatments given were quail given drinking water without a mixture of fermented dragon fruit peel juice (P1), quail given drinking water with a 4% mixture of 619 fermented dragon fruit peel juice (P2), and quail given drinking water with a 6% mixture. fermented fruit peel juice (P3). The variables observed included ration consumption, drinking water consumption, egg weight, egg production, and FCR(Feed Conversion Ratio). The results of this study show that administering fermented dragon fruit peel juice through drinking water as much as 4% and 6% can reduce the FCR value, but is not able to increase ration consumption, drinking water consumption, total egg weight and daily egg production. The conclusion of this research is that the addition of 4% dragon fruit peel juice can be used as a natural supplement to replace AGP.